Focal Scleral Nodule and Scleroderma: report of one case and an observational series - P. Mora; A. Apollonio; A. Ariani; M. Longhena; G. Calzetti; S. Tedesco; S. Gandolfi; M. Angi (Verduci Editore, 2022)
Objective: a) To report an original case of focal scleral nodule (FSN) in a patient affected by collagen's systemic disease; b) to investigate the possible correlation between the two clinical entities by means of an observational case series. Case Presentation: A 74-year-old Caucasian woman was referred on the suspicion of choroidal tumor. She was affected by Systemic Sclerosis (SSc), with a history of an ancient ovarian tumor and a recent severe bacterial pneumonia. Ocular investigations, associated with total body oncological follow up and blood investigations for granulomatous diseases, supported the diagnosis of FSN. Mydriatic fundoscopy was then performed in cohort of 62 eyes of patients affected by confirmed SSc excluding other similar conditions. Conclusions: The simultaneous presence of FSN and SSc has never been reported. The present series has excluded these concomitant findings in a cohort of confirmed SSc subjects. It is probable that SSc alone is not a sufficient condition to promote FSN formation. Further events (e.g., bacterial infections) may play a role in triggering a type 1 collagen over-deposition.